PV Systems with Continuous Sliding Mode Controlled Quadratic Boost Converter. (2016) - Dhanesan, Ashly; Ravishankar, A.N.; Anudev, J.
Abstract: Photovoltaic (PV) systems can provide maximum power with higher efficiency at best operating point with respect to incident solar irradiation. The locus of maximum power operating point varies with panel surface and cell temperature. An effective maximum power point tracking algorithm can always match the solar and load characteristics continuously so that maximum power is transferred to the load. This paper proposes the use of Quadratic Boost Converter (QBC) as a MPPT converter with existing modified incremental conductance algorithm. The performance of the converter is improved with continuous sliding mode controller such that the system is effective for fast and large variations in input solar irradiation. The result is studied in MATLAB/Simulink platform and validates the efficiency of the proposed MPPT controller.